Community-based service use in preschool children with autism spectrum disorder and associations with insurance status. (October 2019) - Rubenstein, Eric; Croen, Lisa; Lee, Li-Ching; Moody, Eric; Schieve, Laura A.; Soke, Gnakub N.; Thomas, Kathleen; Wiggins, Lisa; Daniels, Julie
Highlights: Nearly 40% of preschool age children with ASD in the Study to Explore Early Development received no community-based services. Children on public insurance may be less likely to receive behavior therapy compared to other insurance types. Children on public insurance may be more likely to receive psychotropic medication compared to other insurance types. Abstract: Background: ASD-related services can improve outcomes for children, but less is known about service outside of school settings during preschool age. We aimed to describe amount and category of community-based service use among 3–5-year-old children with ASD and examine differences by health insurance. Methods: We used cross-sectional data on 792 children with ASD diagnoses in the Study to Explore Early Development, a community-based study of neurodevelopment with enrollment between 2012-2016. Mothers reported current child service use and insurance status at study entry. We used log-Poisson and logistic regression to compare service use by insurance group. Results: Nearly 40% of children were not receiving community-based services at study entry. Children with public insurance had fewer total services than children with private or both insurances. After adjustment for sociodemographic confounders, insurance status was not associated with amount of different categories of community-based services. However, children with public insurance alone were least likely to receive community-based behavioral therapy and most likely to receive psychotropic medication compared to other insurances. Conclusion: Many preschool-aged children do not receive community-based services, with receipt of some service types associated with insurance type. Increasing access and availability for evidence-based service, especially for beneficiaries of public insurance, may improve service use and outcomes.